Heterologous intrauterine insemination pregnancy rate using embryo transfer cannula - Hilario, Roly (2013)
Objectives: To determine the heterologous intrauterine insemination (H-IUI), rate of pregnancy by using embryo transfer cannula. Design: Retrospective study. Setting: Procrear Fertility Center, Lima, Peru. Participants: Couples in infertility treatment. Interventions: All H-IUI procedures using sperm bank donor semen from 2007 through September 2010 were studied, all performed by the same gynecologist and the same biologist. IUI was performed using Frydman-Soft embryo transfer cannula with guide following cervix measurement by ultrasound. Rate of pregnancy per cycle and per patient was analyzed as well as factors associated with pregnancy. Epi Info 3.5.1 was used for statistical analysis. Main outcome measures: Pregnancy rate. Results: Thirty H-IUI proceedings were performed in 26 patients with average age 32.6 ± 5.5 years (range: 20-41 years), 40% over 35 years. Pregnancy rate was 40% per cycle and 46% per patient. Most (87%) had only one attempt. Age less than 35 years and 2 to 4 follicles more than 17 mm were related to best results. Having an obstructed tube, endometrial thickness ≤ 6 mm, or insemination after cycle day 15 were associated to negative results. Conclusions: Heterologous IUI with Frydman-Soft embryo transfer cannula provided excellent results in conception and served for training physicians who still do not perform high-complexity procedures. Keywords: Artificial insemination, heterologous, embryo transfer cannula, cryopreserved sperm.